KARAKTERISASI DAN APLIKASI PENANDA MIKROSATELIT PADA BEBERAPA Species Eucalyptus - ILG Nurtjahtjaningsih; AYPBC Widyatmoko; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2013)
Genetically pure species that used as genetic materials represent crucial factors for succeed of a tree improvement strategy. Using microsatellite markers, private allele and genetic variation could genetically distinguish a species. Aims in this study were to  characterize microsatellite markers on Eucalyptus deglupta, E. urophylla and E. pellita, and to assess private allele and genetic variation on the tree Eucalyptus. Results showed that 8, 10 and 12 out of 13 the screened microsatellite markers were amplified and polymorphic on E. deglupta, E. urophylla and E. pellita respectively. Private alleles characterized each  Eucalyptus. Number of detected allele ranged between 29 (E. deglupta) and 91 (E. pellita). Value of expected heterozygosity was lowest on E. deglupta (HE=0.308) and highest on E. pellita (HE=0.604). Coefficient inbreeding value was insignificant deviate from HWE on E. deglupta and E. urophylla, but it was significant on E. pellita. Taxonomy relationship and geographic position in natural distribution each Eucalyptus was discussed. For further study, population genetic and mating system will be important information on the Eucalyptus.